Studying the affected factors to freeze drying process of natto preparation - Tran, Ngoc Khiem; Tran , Thanh Quynh Anh; Nguyen , Tan Dung; Le, Duc Manh (Journal of Technical Education Science, 2016)
Freeze drying process is the drying method which preserves the original biological characteristics of products with high quality compared to other drying methods, providing high efficiency during usage. Natto is known as a product extracted from soybeans fermented by Bacillus Natto bacteria. It is used as a functional food to support stroke people and prevent from disease. Therefore, the freezing drying process was used to study the impacts of factors such as drying temperature, freezing water temperature, pressure, material thickness for preservation of the nutritional composition and biological characteristics of Natto composition. Besides it determines the technological parameters during freeze drying process to increase the velocity of the drying process and shorten the drying time, thereby reducing the energy costs of drying.